2020
DOI: 10.6018/analesps.381181
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and happiness in undergraduate students: Cognitive flexibility and adjustment to university life as mediators

Abstract: De acuerdo con el objetivo del enfoque de psicología positiva, este estudio fue diseñado para construir un modelo de mediación múltiple que permita comprender mejor las relaciones entre optimismo, flexibilidad cognitiva, ajuste a la vida universitaria y felicidad. Un total de 386 estudiantes universitarios (64% mujeres y 36% hombres) entre 18-22 años participaron en el estudio. Los participantes fueron reclutados de una pequeña universidad en Turquía. El Test de Orientación de Vida, el Inventario de Flexibilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 73 publications
(64 reference statements)
2
11
0
7
Order By: Relevance
“…Increased cognitive flexibility may produce well-being in adolescents by enabling them to be more interested in and committed to life activities and tasks, to be more successful in focusing attention, to work tirelessly to achieve the goals, to look at the future with hope, to see the positive aspects of events, to have satisfying relationships with others, to feel more positive emotions, and to be satisfied with life. This result is consistent with the literature showing that cognitive flexibility is positively associated with higher happiness (Asıcı & İkiz, 2015;Demirtaş, 2020b), life satisfaction (Yelpaze & Yakar, 2019;2020); subjective (Satan, 2014), psychological (Malkoç & Kesen Mutlu, 2019), and mental (Demirtaş, 2020a) well-being.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increased cognitive flexibility may produce well-being in adolescents by enabling them to be more interested in and committed to life activities and tasks, to be more successful in focusing attention, to work tirelessly to achieve the goals, to look at the future with hope, to see the positive aspects of events, to have satisfying relationships with others, to feel more positive emotions, and to be satisfied with life. This result is consistent with the literature showing that cognitive flexibility is positively associated with higher happiness (Asıcı & İkiz, 2015;Demirtaş, 2020b), life satisfaction (Yelpaze & Yakar, 2019;2020); subjective (Satan, 2014), psychological (Malkoç & Kesen Mutlu, 2019), and mental (Demirtaş, 2020a) well-being.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Cognitive flexibility was found to be positively related to higher academic, social, emotional, and general self-efficacy (Akçay Özcan & Kıran Esen, 2016; Demirtaş, 2020a), higher resilience (Güleç, 2020), better mental well-being (Demirtaş, 2020a), a greater competence with peers in social relations (Ciairano, Bonino, & Miceli, 2006), less educational stress (Kuyumcu & Kirazcı, 2020), and lower learned helplessness (Taş & Deniz, 2018) in adolescents. In addition, cognitive flexibility was positively associated with happiness (Asıcı & İkiz, 2015;Demirtaş, 2020b), life satisfaction (Yelpaze & Yakar, 2019;2020), subjective wellbeing (Satan, 2014), and psychological well-being (Malkoç & Kesen Mutlu, 2019) in university students. Fu and Chow (2017) indicated that when the adolescents with high cognitive flexibility get hurt during an earthquake, they may experience more psychological well-being than the adolescents with low cognitive flexibility; because they may better tolerate uncertainty, think in a constructive way, and deal with challenges in an effective way.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this can be a challenging experience for students due to the obligations that all this entails [1]. Under this context, previous research has shown that students who have better adapted to the academic environment will perform better academically [2,3]. e research of components related to academic success and student persistence are vitally important issues with regard to higher education [4].…”
Section: Introductionmentioning
confidence: 99%
“…La relación entre la felicidad y el optimismo es mencionada por varios autores analizados en la presente revisión, se trata de un hecho que encuentra eco en los trabajos de Machado et al (2015), Caycho y Castañeda (2015) y Vera-Villarroel y colaboradores (2017); una asociación que puede deberse a que el optimismo promueve mejores estados de ánimo, reacciones adaptativas y constructivas, así como una mejor salud física (Demirtas, 2020). Por otra parte, los trabajos incluidos señalaron una relación entre la felicidad y el sexo; sin embargo, la evidencia empírica acumulada matiza que es una vinculación inconsistente, pues hay estudios reportan mayores niveles de felicidad en mujeres (Arrosa y Gandelman, 2016;Graham et al, 2018), mientras otros los encuentran en hombres (Ahmad y Amin, 2017), o bien, no se encuentran diferencias significativas o al menos no son definitivas entre ambos sexos (Caycho y Castañeda, 2015; Díaz-Loving et al, 2018).…”
Section: Hallazgos De Las Investigacionesunclassified